2003
DOI: 10.1577/1548-8675(2003)023<0462:cotscc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Species Composition, Catch Rate, and Length Distribution of the Catch from Trap Nets with Three Different Mesh and Throat Size Combinations

Abstract: Trap nets of varying design are commonly used to assess fish populations, but the effect of the design on gear selectivity is not well known. In particular, it may be advantageous to use multiple net designs with different mesh and throat sizes to maximize the catch of specific length-classes and to minimize the risk of predation on small fish by larger fish. We compared the species composition, catch rate, and length distribution of fishes caught by three trap net designs with dimensions differing only in mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
34
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 11 publications
3
34
0
Order By: Relevance
“…Our results support the recommendations of Van Den Avyle et al (1995) that the preferred method of sampling will depend on the fish size-range and habitat being sampled. We also agree with Shoup et al (2003), that multiple gear types are preferable when sampling to assess size-frequency or abundance estimates, and Krause et al (2002) that sampling should be carried out over a range of seasons to reduce estimate error.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our results support the recommendations of Van Den Avyle et al (1995) that the preferred method of sampling will depend on the fish size-range and habitat being sampled. We also agree with Shoup et al (2003), that multiple gear types are preferable when sampling to assess size-frequency or abundance estimates, and Krause et al (2002) that sampling should be carried out over a range of seasons to reduce estimate error.…”
Section: Discussionsupporting
confidence: 77%
“…Several authors attribute the bias to fish escapement (Jacobsen and Kushlan, 1987;Losanes et al, 1992;Bayley and Herendeen, 2000). Others (Allen et al, 1992;Shoup et al, 2003) have attributed the bias to avoidance behaviour, particularly by larger fish. In our study, large sea mullet (Mugil cephalus) were observed to leap over the net during setting on several occasions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shoup et al (2003) advised against the value of comparing population or community structure data that had been obtained by different passive methods. PM traps are the most easily repeatable, as well as the cheapest, among the four trap types employed.…”
Section: Discussionmentioning
confidence: 99%
“…Gear configuration, such as different fyke net meshes and shape (e.g., Krueger et al 1998;Shoup et al 2003), has previously been studied. However, the effect of different gear deployments on catch and resulting fish community descriptors, especially in areas with a diversity of habitats, has not been fully explored.…”
mentioning
confidence: 99%